Spontaneous vertebral artery dissection: Posterior circulation stroke - Manoj Deshmukh; Anju Wadhwa; Ravi Rajdeo (Journal of Craniovertebral Junction and Spine, 2015)
Spontaneous vertebral artery dissection (VAD) is relatively rare but an important cause of posterior circulation stroke. A 46-year-male complaining of sudden onset headache, neck pain with right-sided neuro deficit in the form of hemiparesis was evaluated by contrast magnetic resonance imaging and dual-energy computed tomography (CT) and brain neck angiography which revealed a short segment extracranial left-sided VAD, associated with acute infarct in the left occipital region. The patient was managed conservatively and followed up for 6 months. Follow-up CT angiography after a period of 6 months revealed the near complete resolution of the arterial dissection in left vertebral artery.